Fifteen-year study of environmental dredging effect on variation of nitrogen and phosphorus exchange across the sediment-water interface of an urban lake. (December 2016) - Liu, Cheng; Zhong, Jicheng; Wang, Jianjun; Zhang, Lu; Fan, Chengxin
Abstract: Environmental dredging has been applied widely in Chinese lakes to reduce their internal nutrient loads. However, the efficacy of dredging to reduce internal loading of nitrogen (N) and phosphorus (P) and to improve water quality has been questioned by some researchers. In this study, the long-term (∼15 years) effects of dredging to reduce internal N and P loading in a closed, polluted urban lake were investigated. The results showed that the release of soluble reactive phosphorus (SRP) could be suppressed quickly after dredging, and that the dredging effect was sustained for about 18 months. A significant release of NH4 + -N was discovered during the first 2–8 months after dredging, followed by maintenance of low-level release rates for about 21–32 months. The continuous inflowing of external pollution loading led to the increase in the release rates of SRP and NH4 + -N. The external pollution loading was therefore reduced three years after dredging to strengthen the remediation effect. After that, high diffusive flux from the sediment was observed for both NH4 + -N and SRP during summer seasons for about six years, followed by a decreasing trend. The NH4 + -N concentration in the overlying water was reduced after the reduction of external loading, while a high concentration of SRP in the overlying water was still observed during summer seasons. In conclusion, the mid-term (<3 years) reduction of internal N and P loading could be achieved by dredging if the external pollution loading were not reduced. Achieving long-term control would require modification of external loading. Highlights: Effect of dredging on reduction of N and P loading was studied for 15 years. Release of SRP was suppressed soon after dredging and restrained for 18 months. Major release of NH4 + -N occurred 2–8 months after dredging; less for 21–32 months. Long-term control by dredging requires limiting external loading of pollutants. Long-term control of N in water was more effective than that of P in the lake. Abstract : The use of dredging for mid-term reduction of internal nitrogen and long-term control of nitrogen in the water was more effective than its use for control of phosphorus.